A high performance Sc-based nanoprobe for through-skull fluorescence imaging of brain vessels beyond 1500 nm. Issue 19 (9th May 2018) - Deng, Zhiming; Li, Xiaolong; Xue, Zhenluan; Jiang, Mingyang; Li, Youbin; Zeng, Songjun; Liu, Hongrong
Abstract : PAA-KSc2 F7 nanoprobes with good biocompatibility and controlled size were developed for brain blood vessel fluorescence imaging beyond 1500 nm. Abstract : Optical bioimaging that works in the second near infrared region (NIR-II, 1000–1700 nm) has emerged as a next generation imaging technique with superior imaging sensitivity and spatial resolution compared to traditional optical imaging utilizing visible and near-infrared lights (below 900 nm). Herein, a new Sc-based NIR-II probe was explored for high performance NIR-II in vivo bioimaging and optical imaging-guided non-invasive brain blood vessel visualization. The lanthanide doped Sc-based probes (KSc2 F7 :Yb 3+ /Er 3+ ) possess a pure orthorhombic phase structure with size control by adjusting the F − ion content. These probes present a dominant red upconversion (UC) emission, which is significantly different from the traditional NaYF4 :Yb/Er host, which usually has a green UC emission. More importantly, apart from the dominant red UC emission, these probes also possess a strong NIR-II downconversion (DC) emission centered at 1525 nm, which is usually ignored for bioimaging applications. In vivo NIR-II imaging reveals that our explored Sc-based nanorods are promising probes for highly sensitive optical imaging. Moreover, non-invasive through-skull fluorescence bioimaging of brain vessels with high spatial resolution was demonstrated. Therefore, it is expected that Sc-based nanomaterials with unique dominant red UC and DC NIR-II emissions beyond 1500 nm are ideal probes for bio-applications.